Evaluation of the Relationships between Chronological Age, Skeletal Maturation, Dental Maturation, and Sagittal Jaw Relationships - Gülşilay Sayar Torun; Hüsamettin Oktay (Galenos Yayinevi, 2015)
Objective:The present study aimed to determine whether there is a correlation between chronological age, skeletal maturation, dental maturation, and ANB angle.Methods:Lateral cephalometric, panoramic, and hand-wrist radiographs of 200 orthodontic patients were used (100 males and 100 females; mean age 13.00 and 13.70 years, respectively). Skeletal maturation was determined by two different methods: cervical vertebral maturation (CVM) and the hand-wrist radiography method of Grave-Brown. Dental maturation was defined by the Demirjian Index using the mandibular canine, premolars, and second molar on the left side. The ANB angle was measured on lateral cephalometric head films. The data were analyzed by Spearman's rank correlation analysis.Results:Correlation coefficients of the male and female subjects were 0.825 and 0.802 between chronological age and hand-wrist evaluation; 0.744 and 0.778 between chronological age and CVM evaluation; 0.677 and 0.443 between chronological age and mandibular canine development; 0.722 and 0.458 between chronological age and mandibular first premolar development; 0.730 and 0.517 between chronological age and mandibular second premolar development; 0.701 and 0.531 between chronological age and mandibular second molar development; and −0.183 and −0.045 between chronological age and ANB, respectively. All the correlations mentioned above were statistically significant (p<0.001), except for the last one.Conclusions:High correlations were found between the chronological age, hand-wrist, and cervical vertebral maturation evaluations. Chronological age was also correlated with dental maturation, particularly in mandibular second molars. There was no correlation between ANB and the other parameters.